A bifunctional nuclear grade strong acid cation exchange resin for efficient adsorption of electronic grade pyridine and a preparation method thereof
Patent Information
- Application Number
- CN202611385917.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-27
AI Technical Summary
普通纯度的吡啶若含有微量水分或金属杂质,不仅会直接导致光刻图案发生漂移、影响薄膜成膜的均匀性,更可能在半导体晶格中诱发缺陷,从而导致终端产品的电学性能失效
本发明通过以核子级强酸性阳离子交换树脂为基体,经盐酸淋洗、洗涤至中性、脱水和干燥处理后,在醇相中接枝含磺基甜菜碱结构的两性离子功能层,再经羟胺改性引入羟肟酸基团,得到了一种兼具磺基甜菜碱基团和羟肟酸基团的双功能吸附树脂,可实现对电子级吡啶中多类型杂质的协同去除。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic chemical purification materials technology, and in particular to a bifunctional nuclear-grade strong acid cation exchange resin for efficient adsorption of electronic-grade pyridine and its preparation method. Background Technology
[0002] With the rapid development of high-end manufacturing industries such as semiconductors, display panels, and new energy materials, the purity requirements for electronic chemicals are constantly increasing, especially for high-purity organic solvents used in key processes such as photolithography, cleaning, and wet etching. Pyridine (C5H5N), as a highly polar aprotic solvent and a basic organic base, occupies an irreplaceable strategic position in the field of electronic chemicals. The essential difference between electronic-grade pyridine and industrial-grade and pharmaceutical-grade pyridine lies in its ultra-high purity and extremely low trace impurity content. Typically, its purity requirement is not less than 99.99%, and key metal ions (such as Na) are also present. + K + Ca 2+ The concentration of pyridine (electro-grade pyridine) needs to be controlled below 1 ppb (parts per billion) or even 10 ppt. In the manufacturing processes of semiconductor integrated circuits, large-size liquid crystal display panels (TFT-LCD), and organic light-emitting diodes (OLED), electronic-grade pyridine mainly serves as an ultra-cleaning agent, a photoresist diluent / modifier, and a catalyst or ligand for chemical vapor deposition (CVD) and atomic layer deposition (ALD). With the continuous evolution of advanced process nodes (such as 7nm, 5nm and below), the tolerance threshold of electronic components to trace metal impurities and particulate contamination has been reduced to the limit. If ordinary purity pyridine contains trace amounts of moisture or metal impurities, it will not only directly cause photolithographic pattern drift and affect the uniformity of thin film formation, but may also induce defects in the semiconductor lattice, thereby causing the electrical performance failure of the end product.
[0003] However, due to the tendency of pyridine molecules to form azeotropes with water and their similar boiling points to their homologues (such as methylpyridine), the large-scale preparation of ultra-high purity electronic-grade pyridine faces extremely high technological barriers. Currently, this high-end market has long been dominated by a few chemical companies, whose core technologies are concentrated in multi-stage precision vacuum distillation, deep purification using selective ion exchange resins, and ultra-clean filling processes. Therefore, research on purification processes for electronic-grade pyridine and its application in the modification of downstream high-sensitivity ion adsorption resins has become an important direction for breaking through the predicament of high-end electronic materials and achieving independent control of the entire microelectronics process industry chain. Summary of the Invention
[0004] The purpose of this invention is to provide a bifunctional nucleo-level strong acid cation exchange resin for efficient adsorption of electronic-grade pyridine and its preparation method, thereby solving the aforementioned problems in the background art. This invention introduces sulfobetaine functional groups into the resin surface and / or pores, which can enhance the resin surface's polar affinity and adsorption capacity for polar impurities, facilitating the enrichment of polar impurities and trace ionic impurities in electronic-grade pyridine at the resin interface. The introduction of hydroxamic acid functional groups allows for the formation of coordination complexes with various trace metal ions in electronic-grade pyridine, improving the resin's removal capacity for complexed metals, transition metal ions, and polyvalent metal ions.
[0005] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of this invention is to provide a method for preparing a bifunctional nucleo-level strong acid cation exchange resin for efficient adsorption of electronic-grade pyridine, comprising the following steps: (1) Pretreatment of nuclear-grade resin: Take nuclear-grade strong acid cation exchange resin and sequentially perform hydrochloric acid rinsing, washing until neutral, dehydration and drying to obtain matrix resin; (2) Grafting sulfobetaine functional groups: The matrix resin is dispersed in isopropanol, sulfobetaine monomer and free radical initiator are added, and the reaction is carried out under a protective atmosphere by heating and stirring. Then the resin is washed and dried to obtain sulfobetaine modified resin. (3) Grafting hydroxamic acid functional groups: The sulfobetaine-modified resin is dispersed in a solvent, hydroxylamine aqueous solution is added, the pH is adjusted to alkaline, heated to react, washed and dried to obtain sulfobetaine-hydroxamic acid bifunctional adsorption resin.
[0006] Preferably, in step (1): the hydrochloric acid rinsing is electronic grade hydrochloric acid rinsing; the washing to neutrality is ultrapure water rinsing to neutrality; the dehydration is dehydration with electronic grade ethanol; and the drying treatment is vacuum drying treatment.
[0007] More preferably, the concentration of the electronic-grade hydrochloric acid used for rinsing is 0.8–1.2 mol / L, more preferably 1.0 mol / L, and the amount used is 2.5–3.5 BV, more preferably 3 BV; the temperature of the vacuum drying treatment is 38–42°C, more preferably 40°C, and the time is 5–7 h, more preferably 6 h.
[0008] Preferably, the nuclear-grade strong acid cation exchange resin is a sulfonic acid type styrene-divinylbenzene copolymer resin, more preferably an H-type nuclear-grade strong acid cation exchange resin, wherein the total background metal ion content of the resin is ≤100 ppt, the degree of crosslinking is 8-12%, and the particle uniformity is ≥95%.
[0009] More preferably, the nuclear-grade strong acid cation exchange resin is one of LEWATIT® MonoPlus S 200 KR, AmberLite™ IRN99 H and AmberLite™ IRN77 H.
[0010] Preferably, the sulfobetaine monomer is a sulfobetaine monomer containing an acrylamide structure, more preferably N,N-dimethyl-N-acrylamidopropylsulfobetaine; the free radical initiator is an azo initiator, more preferably azobisisobutyronitrile.
[0011] More preferably, in step (2), the ratio of the matrix resin to isopropanol is 100 g: 180-220 mL, more preferably 100 g: 200 mL.
[0012] More preferably, in step (2), the mass ratio of the matrix resin, sulfobetaine monomer and free radical initiator is 100:4.5-6.0:0.35-0.45, more preferably 100:5.0:0.4.
[0013] Preferably, before the heating and stirring reaction, the system is further subjected to nitrogen purging three times.
[0014] Preferably, in step (2), the temperature of the heating and stirring reaction is 68-72℃, more preferably 70℃, and the time is 6.5-7.5 h, more preferably 7 h.
[0015] Preferably, in step (2): the washing is performed by washing with ultrapure water until no free hydroxylamine is present; the drying is performed by vacuum drying, and the temperature of the vacuum drying is 38-42℃, more preferably 40℃.
[0016] Preferably, in step (3): the solvent contains methanol and water in a volume ratio of 0.8-1.2:1, more preferably methanol and water in a volume ratio of 1:1; the ratio of the amount of the sulfobetaine-modified resin to the solvent is 100 g: 250-350 mL, more preferably 100 g: 300 mL.
[0017] Preferably, in step (3): the concentration of the hydroxylamine aqueous solution is 12-14 wt%, more preferably 12 wt%; the amount of the hydroxylamine aqueous solution is 4.5-5.5 times the mass of the sulfobetaine-modified resin, more preferably 5 times; adjusting the pH to alkalinity is adjusting the pH to 7.8-8.2, more preferably 8.0; the washing is alternating washing with electronic grade ethanol and ultrapure water; the drying is vacuum drying, and the temperature of the vacuum drying is 38-42℃, more preferably 40℃.
[0018] Preferably, in step (3), the temperature of the heating reaction is 48-52℃, more preferably 50℃, and the time is 9-11h, more preferably 10h.
[0019] The second technical solution of the present invention provides a bifunctional nucleo-level strong acid cation exchange resin for efficient adsorption of electronic-grade pyridine, obtained according to the above preparation method.
[0020] The bifunctional adsorption resin of the present invention uses a nuclear-level strong acid cation exchange resin as a matrix, and sulfobetaine functional groups and hydroxamic acid functional groups are grafted onto the surface and / or pores of the matrix resin.
[0021] The third technical solution of the present invention provides an application of the above-mentioned bifunctional nucleo-level strong acid cation exchange resin for efficient adsorption of electronic-grade pyridine in the purification of electronic-grade pyridine.
[0022] Preferably, the electronic-grade pyridine is pyridine for semiconductor cleaning or pyridine for liquid crystal materials.
[0023] The beneficial technical effects of the present invention are as follows: This invention utilizes a nuclear-grade strongly acidic cation exchange resin as a matrix. After rinsing with hydrochloric acid, washing to neutrality, dehydration, and drying, an amphoteric functional layer containing a sulfobetaine structure is grafted onto the alcohol phase. Then, hydroxylamine modification is used to introduce hydroxamic acid groups, resulting in a bifunctional adsorption resin with both sulfobetaine and hydroxamic acid groups. This resin can achieve synergistic removal of multiple types of impurities in electronic-grade pyridine.
[0024] This invention introduces sulfobetaine functional groups into the resin surface and / or pores, which can be used to improve the polar affinity of the resin surface and the adsorption of polar impurities, thus facilitating the enrichment of polar impurities and trace ionic impurities in electronic-grade pyridine to the resin interface. The introduction of hydroxamic acid functional groups is used to form coordination complexes with various trace metal ions in electronic-grade pyridine, thereby improving the resin's ability to remove complexed metals, transition metal ions, and polyvalent metal ions.
[0025] This resin exhibits low background metal content, high purity, and low soluble content. It features low metal precipitation, low organic leaching, a polar-affinity surface, strong complexing and coordination ability, and good compatibility with organic solvents. It is suitable for the deep purification of trace metal ions, polar impurities, and complexable impurities in high-purity organic solvents such as electronic-grade pyridine. This invention also provides a method for preparing this resin and its application in the purification of electronic-grade pyridine. The preparation method uses mild conditions, easily removable solvents, and a low reaction temperature, making it suitable for large-scale preparation and continuous column purification. Detailed Implementation
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0027] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0028] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. It should be noted that any aspects of this invention not described in detail are conventional practices in the art and are not the focus of this invention.
[0029] The terms “comprising,” “including,” “having,” “containing,” etc., used in this invention are all open-ended terms, meaning that they include but are not limited to.
[0030] Unless otherwise specified, "room temperature" in this invention refers to 20±10℃.
[0031] All raw materials used in the following embodiments and comparative examples of the present invention are commercially available products.
[0032] The technical solution of the present invention will be further illustrated by the following embodiments.
[0033] The LEWATIT® MonoPlus S 200 KR nuclear-grade strong acid cation exchange resin used in this invention has a background metal ion content ≤100ppt, a crosslinking degree of 8-12%, and a particle uniformity ≥95%.
[0034] Example 1 A method for preparing a bifunctional nucleo-level strong acid cation exchange resin for efficient adsorption of electronic-grade pyridine, comprising the following steps: 1. Nuclear-grade resin pretreatment Weigh 100 g of LEWATIT® MonoPlus S 200 KR nuclear-grade strong acid cation exchange resin (purchased from Lanxess, Germany) and pack it into a clean glass column. Elute with 1 mol / L electronic-grade hydrochloric acid at a rate of 3 BV (bed volume). After acid washing, continuously rinse with ultrapure water until the pH of the effluent is close to neutral. Transfer the resin to a clean container, add electronic-grade ethanol to wet and dehydrate, filter, and vacuum dry at 40°C for 6 h to obtain the H-type matrix resin.
[0035] 2. Grafted sulfobetaine 100 g of the H-type matrix resin was added to a reactor equipped with a stirrer, condenser, and nitrogen protection device. 200 mL of electronic-grade isopropanol was added to fully disperse the resin. 5.0 g of N,N-dimethyl-N-acrylamidopropyl sulfobetaine and 0.4 g of azobisisobutyronitrile were added to the system. After purging the reaction system with nitrogen three times, the mixture was stirred at 70 °C for 7 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the resin was collected. It was then washed alternately with electronic-grade ethanol and ultrapure water until no obvious monomer or organic residues were detected in the washings. The washed resin was vacuum dried at 40 °C to obtain the sulfobetaine-modified resin.
[0036] 3. Grafted hydroxamic acid group 100g of the sulfobetaine-modified resin obtained in step 2 was added to a reactor, along with 300 mL of a methanol / water mixed solvent (methanol to water volume ratio 1:1). The mixture was stirred to ensure uniform dispersion of the resin. A 12 wt% hydroxylamine aqueous solution was added, with the amount of hydroxylamine aqueous solution being 5 times the mass of the sulfobetaine-modified resin. The pH of the system was adjusted to 8.0 using high-purity ammonia, and the reaction was carried out at 50℃ for 10 h. After the reaction was completed, the resin was collected by filtration and repeatedly washed with ultrapure water until no free hydroxylamine was detected in the washings. Finally, the resin was vacuum dried at 40℃ to obtain the sulfobetaine-hydroxyxamic acid bifunctional adsorption resin.
[0037] Example 2 This embodiment is basically the same as Example 1, except that: in step 1, the nuclear-grade resin matrix is AmberLite™ IRN99 H (purchased from DuPont Dennemo); in step 2, the amount of N,N-dimethyl-N-acrylamidopropyl sulfobetaine added is 3.0 g, the amount of azobisisobutyronitrile added is 0.3 g, the reaction temperature is 65℃, and the reaction time is 8 h; in step 3, the hydroxylamine aqueous solution has a mass fraction of 10 wt%, the amount used is 4 times the mass of the resin, the pH is adjusted to 7.5, the reaction temperature is 45℃, and the reaction time is 12 h.
[0038] Test results show that the resin obtained in Example 2 has a low amount of functional layer grafting, making it suitable for the purification process of electronic-grade pyridine with high requirements for low dissolution and low impurity load.
[0039] Example 3 This embodiment is basically the same as Example 1, except that: in step 2, the amount of N,N-dimethyl-N-acrylamidopropyl sulfobetaine added is 8.0 g, the amount of azobisisobutyronitrile added is 0.5 g, the reaction temperature is 75℃, and the reaction time is 6 h; in step 3, the mass fraction of hydroxylamine aqueous solution is 15 wt%, the amount used is 6 times the mass of resin, the pH is adjusted to 8.5, the reaction temperature is 55℃, and the reaction time is 8 h.
[0040] Test results show that the resin obtained in Example 3 has a high density of functional groups and is suitable for the purification of electronic-grade pyridine with relatively high content of trace metal impurities or requiring enhanced complexation adsorption.
[0041] Example Performance Testing 50 mL of the treated resin from Examples 1-3 was packed into a 20 mm inner diameter PFA chromatography column. The pyridine to be purified was fed through the resin bed at a space velocity of 2 BV / h (bed volume / hour) under nitrogen atmosphere at 25°C. After discarding the initial 1 BV eluent, subsequent eluent samples were collected, and the concentrations of each metal ion were determined by inductively coupled plasma mass spectrometry (ICP-MS). The results were compared with the initial background concentration of trace metal ions in the pyridine to be purified. The results are shown in Table 1.
[0042] Table 1. Adsorption performance of the bifunctional modified ion adsorption resins in Examples 1-3 Comparative Example 1 This comparative example is basically the same as Example 1, except that: a nuclear-grade strong acid cation exchange resin (i.e., the "H-type matrix resin" in Example 1) that has not been modified with sulfobetaine and hydroxamic acid is used as the adsorbent material.
[0043] The pyridine to be purified was purified by column chromatography in the same manner as in the "Performance Test of Examples". The test results of Comparative Example 1 show that, compared with the bifunctional adsorption resin obtained in Example 1, the unmodified nuclear-grade strong acid cation exchange resin mainly relies on sulfonic acid group ion exchange, and its ability to remove complexed metal ions and some polar impurities is weak.
[0044] Comparative Example 2 This comparative example is basically the same as Example 1, except that: a resin modified only by sulfobetaine and not by hydroxamic acid (i.e., the "sulfobetaine-modified resin" in Example 1) is used as the adsorbent material.
[0045] The pyridine to be purified was purified by column chromatography in the same manner as in the "Performance Test of Examples". The test results of Comparative Example 2 showed that, compared with the bifunctional adsorption resin obtained in Example 1, the resin containing only the sulfobetaine functional layer, although having a better polar affinity interface, lacked strong coordination complexing sites provided by the hydroxamic acid group, and thus had insufficient ability to deeply remove some transition metals and polyvalent metal ions.
[0046] Comparative Example 3 This comparative example is basically the same as Example 1, except that a resin modified with only hydroxamic acid groups is used as the adsorbent. The specific preparation method is as follows: The sulfobetaine-modified resin added in step 3 was replaced with an equal mass of the H-type matrix resin prepared in step 1 of Example 1.
[0047] The pyridine to be purified was purified by column chromatography in the same manner as in the "Performance Test of Examples". The test results of Comparative Example 3 show that, compared with the bifunctional adsorption resin obtained in Example 1, although the single hydroxamic acid functional resin has a certain metal complexing ability, the affinity of the resin interface is insufficient. When treating pyridine for a long time, the adsorption efficiency may decrease or impurity competitive adsorption may occur.
[0048] Comparative performance test 50 mL of the treated resin from Comparative Examples 1-3 was packed into a 20 mm inner diameter PFA chromatography column. Under nitrogen atmosphere at 25 °C, the pyridine to be purified was passed through the resin bed at a space velocity of 2 BV / h (bed volume / hour). After discarding the initial 1 BV eluent, subsequent eluent samples were collected, and the concentrations of each metal ion were determined by inductively coupled plasma mass spectrometry (ICP-MS). The results were compared with the initial background concentrations of trace metal ions in the pyridine to be purified. The results are shown in Table 2.
[0049] Table 2 Adsorption performance of ion adsorption resins in Comparative Examples 1-3 Table 2 shows that Comparative Example 1 mainly relies on sulfonic acid group ion exchange, and has a certain removal ability for ionic impurities such as Na, Mg, K, and Ca, but its ability to deeply remove complexed metals such as Cr, Fe, Ni, Cu, and Zn is insufficient. Comparative Example 2, due to the introduction of a sulfobetaine functional layer, has increased resin surface polarity, resulting in better removal of ionic impurities such as Na, Mg, K, and Ca, but lacks strong hydroxamic acid complexing sites, limiting its removal of transition metal ions. Comparative Example 3 contains hydroxamic acid groups, showing good removal effects for transition metals and polyvalent metal ions such as Cr, Fe, Ni, Cu, and Zn, but due to the lack of a sulfobetaine polar interface, its synergistic removal ability for ionic impurities such as Na, Mg, K, and Ca is weak.
[0050] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for preparing a bifunctional nucleo-level strong acid cation exchange resin for efficient adsorption of electronic-grade pyridine, characterized in that, Includes the following steps: (1) Take nuclear-grade strong acid cation exchange resin and sequentially perform hydrochloric acid rinsing, washing until neutral, dehydration and drying to obtain matrix resin; (2) The matrix resin is dispersed in isopropanol, sulfobetaine monomer and free radical initiator are added, and the mixture is heated and stirred under a protective atmosphere. Then it is washed and dried to obtain sulfobetaine modified resin. (3) Disperse the sulfobetaine-modified resin in a solvent, add an aqueous hydroxylamine solution, adjust the pH to alkaline, heat the reaction, wash and dry to obtain the nuclear-grade resin-based bifunctional adsorption resin for the purification of electronic-grade pyridine.
2. The preparation method according to claim 1, characterized in that, In step (1): the nuclear-grade strong acid cation exchange resin is a sulfonic acid type styrene-divinylbenzene copolymer resin.
3. The preparation method according to claim 1, characterized in that, The sulfobetaine monomer is a sulfobetaine monomer containing an acrylamide structure; the free radical initiator is an azo initiator.
4. The preparation method according to claim 1, characterized in that, In step (2): the ratio of the matrix resin to isopropanol is 100 g: 180-220 mL; The mass ratio of the matrix resin, sulfobetaine monomer, and free radical initiator is 100:4.5-6.0:0.35-0.
45.
5. The preparation method according to claim 1, characterized in that, In step (2): the temperature of the heating and stirring reaction is 68-72℃ and the time is 6.5-7.5 h.
6. The preparation method according to claim 1, characterized in that, In step (3): the solvent contains methanol and water in a volume ratio of 0.8-1.2:1; the ratio of the amount of the sulfobetaine-modified resin to the solvent is 100 g: 250-350 mL.
7. The preparation method according to claim 1, characterized in that, In step (3): the concentration of the hydroxylamine aqueous solution is 12-14 wt%; the amount of the hydroxylamine aqueous solution is 4.5-5.5 times the mass of the sulfobetaine-modified resin; and the pH is adjusted to alkaline by adjusting the pH to 7.8-8.
2.
8. The preparation method according to claim 1, characterized in that, In step (3): the heating reaction temperature is 48-52℃ and the time is 9-11 h.
9. A bifunctional nucleo-level strong acid cation exchange resin for efficient adsorption of electronic-grade pyridine, obtained by the preparation method according to any one of claims 1-8.
10. The application of the bifunctional nucleo-level strong acid cation exchange resin for efficient adsorption of electronic-grade pyridine as described in claim 9 in the purification of electronic-grade pyridine.